Theoretical physics and astrophysics - Ginzburg, V. L. (Vitalii Lazarevich), 1916-2009 (International series in natural philosophy, 1979)
The aim of this book is to present, on the one hand various topics in theoretical physics in depth - especially topics related to electrodynamics - and on the other hand to show how these topics find applications in various aspects of astrophysics. The first text on theoretical physics and astrophysical applications, it covers many recent advances including those in X-ray, -ray and radio-astronomy, with comprehensive coverage of the literature.